2016
DOI: 10.1116/1.4971173
|View full text |Cite
|
Sign up to set email alerts
|

Alumina films as gas barrier layers grown by spatial atomic layer deposition with trimethylaluminum and different oxygen sources

Abstract: Alumina layers were grown from trimethylaluminum (TMA) and water, ozone as well as an oxygen plasma as co-reactants in low temperature spatial atomic layer deposition (ALD). The influence of the amount of precursor, the precursor exposure duration, and substrate temperature were investigated with respect to the growth rate while employing different oxygen sources. The TMA/water process provided alumina (AlOx) films with superb film quality as shown by infrared measurements. Ozone-based processes allowed lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…To date, SALD has been extensively used for encapsulation, to protect devices or to fabricate gas diffusion barriers, both in rigid and flexible substrates, including paper, as detailed below. [44,48,64,[66][67][68][69][70][71][72][73] Choi et al have demonstrated Al2O3 deposition rates as high as 7 nm/min (0.12 nm/s) at temperatures below 100 °C. The SALD system they have developed is coupled to a glove box and can coat substrates of industrial size (370 x 470 mm 2 ).…”
Section: Spatial Aldmentioning
confidence: 99%
“…To date, SALD has been extensively used for encapsulation, to protect devices or to fabricate gas diffusion barriers, both in rigid and flexible substrates, including paper, as detailed below. [44,48,64,[66][67][68][69][70][71][72][73] Choi et al have demonstrated Al2O3 deposition rates as high as 7 nm/min (0.12 nm/s) at temperatures below 100 °C. The SALD system they have developed is coupled to a glove box and can coat substrates of industrial size (370 x 470 mm 2 ).…”
Section: Spatial Aldmentioning
confidence: 99%
“…This spatially separated exposure of the substrate is equivalent to the temporal ALD cycles and achieves comparable materials properties when the materials deposited are not sensitive to the atmosphere [7]. SALD has been tested before by several groups to deposit a wide variety of functional oxides in a homogeneous and conformal manner, in many cases taking place at atmospheric pressure [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous approaches have been explored to successfully generate the mentioned spatial regions needed, without intermixing the gaseous precursors in SALD [9][10][11][12]. Specifically, the approach used in our laboratory (a home-made system presented and explained in detail in [4]) is based on a patent published by Kodak [13] that led to the publication of scientific papers using the spatial separation ALD concept by the same group from 2008 [4].…”
Section: Introductionmentioning
confidence: 99%
“…The barrier property of the PEN substrates coated with 100-nm-thick nanolaminates improved from 1.8 Â 10 À3 to 6.9 Â 10 À5 g/m 2 Áday [137]. Franke et al developed their SALD system integrated with a microwave plasma source, and the WVTR value of 50 nm Al 2 O 3 could reach ;10 À6 g/m 2 Áday [56]. Due to the simplicity of the linear track one, we also developed the modular injector integrated SALD apparatus, and the deposition rate reached 100 nm/min with the nonuniformity around 2% [138].…”
Section: Ald Reactors and Processes For Tfementioning
confidence: 99%